Mechanism Investigation and Clinical Retrospective Evaluation of Qingyi Granules: Pancreas Cleaner About Ameliorating Severe Acute Pancreatitis with Acute Respiratory Distress Syndrome - Ge P; Luo Y; Zhang J; Liu J; Xu C; Guo H; Gong A; Zhang G; Chen H (Dove Medical Press, 2024)
Peng Ge,1- 3,* Yalan Luo,3,* Jinquan Zhang,1- 3,* Jie Liu,1- 3 Caiming Xu,1,4 Haoya Guo,1- 3 Aixia Gong,3 Guixin Zhang,1- 3 Hailong Chen1- 3 1Department of General Surgery, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People's Republic of China; 2Institute (College) of Integrative Medicine, Dalian Medical University, Dalian, Liaoning, People's Republic of China; 3Laboratory of Integrative Medicine, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People's Republic of China; 4Department of Molecular Diagnostics and Experimental Therapeutics, Beckman Research Institute of City of Hope, Biomedical Research Center, Comprehensive Cancer Center, Duarte, CA, USA*These authors contributed equally to this workCorrespondence: Guixin Zhang; Hailong Chen, Email zgx0109@126.com; chenhailong@dmu.edu.cnBackground: Despite its extensive utilization in Chinese hospitals for treating acute pancreatitis (AP) and related acute respiratory distress syndrome (ARDS), the active components and mechanisms underlying the action of Qingyi Granule (QYKL) remain elusive.Methods: This study consists of four parts. First, we used Mendelian randomization (MR) to investigate the causal relationship between AP, cytokine, and ARDS. Next, 321 patients were collected to evaluate the efficacy of QYKL combined with dexamethasone (DEX) in treating AP. In addition, we used UHPLC-QE-MS to determine the chemical constituents of QYKL extract and rat serum after the oral administration of QYKL. The weighted gene coexpression network analysis (WGCNA) method was used to find the main targets of AP-related ARDS using the GSE151572 dataset. At last, a AP model was established by retrograde injection of 5% sodium taurocholate.Results: MR showed that AP may have a causal relationship with ARDS by mediating cytokine storms. Retrospective study results showed early administration of QYKL was associated with a lower incidence of ARDS, mortality, admissions to the intensive care unit, and length of stay in AP patients compared to the Control group. Furthermore, we identified 23 QYKL prototype components absorbed into rat serum. WGCNA and differential expression analysis identified 1558 APALI-related genes. The prototype components exhibited strong binding activity with critical targets. QYKL has a significant protective effect on pancreatic and lung injury in AP rats, and the effect is more effective after combined treatment with DEX, which may be related to the regulation of the IL-6/STAT3 signaling pathway.Conclusion: By integrating MR, retrospective analysis, and systematic pharmacological methodologies, this study systematically elucidated the therapeutic efficacy of QYKL in treating AP-related ARDS, establishing a solid foundation for its medicinal use. Keywords: acute pancreatitis, qingyi granule, dexamethasone, acute lung injury, clinical efficacy, Mendelian randomization, rat